Transport of Nitric Oxide in the Winter Mesosphere and Lower Thermosphere - H.‐L. Liu (Geophysical Research Letters)
Abstract Nitric oxide (NO) plays key roles both in thermospheric energetics and upper‐lower atmosphere coupling. However, mesospheric NO in the polar night region has often been underestimated in whole atmosphere models, and the exact causes are not well understood. Recent high‐resolution (HR) WACCM‐X simulations show significant increase in NO in the polar night, and our analysis reveals distinct differences in the vertical transport between the HR and coarse resolution (CR) simulations: The residual mean vertical wind in the mesosphere and lower thermosphere (MLT) region displays mesoscale flow channels that are strong and alternate between upward and downward directions in the former, with large net downward transport over the polar region. In the latter it is much weaker and even upward over large latitude ranges. Moreover, the resolved waves in the HR simulations induce downward eddy transport of NO in the MLT much stronger than the parameterized diffusion in CR simulations.